Preparation strategies of mussel-inspired chitosan-based biomaterials for hemostasis - Cui, Guihua; Guo, Xiaoyu; Deng, Li (Frontiers in Pharmacology, 2024)
Chitosan (CS) has been extensively studied in wound care for its intrinsic hemostatic and antibacterial properties. However, CS has limiting hemostasis applications on account of its drawbacks such as poor adhesion in humid environments and water solubility at neutral pH. CS-based biomaterials inspired by mussel-adhesive-proteins, is a suggested platform by biomedical science. The reports show that mussel-inspired CS-based hemostatic structure has negligible toxicity and excellent adhesiveness. Biomedicine has witness significant progress in the development of this hemostatic materials. This review summarizes the methods for the modification of CS by mussel-inspired chemistry. Moreover, the general method for preparation of mussel-inspired CS-based biomaterials were briefly discussed in this review. This work is expected to give a better understanding of opportunities and challenges of mussel-inspired strategy for the functionalization of CS-based biomaterials in hemostasis and wound healing. This review is hoped to provide an important perspective on the preparation of mussel- inspired for CS-based hemostatic materials.